Pengaruh After Sales Service dan Personal Selling Terhadap Keputusan Pembelian Sepeda Motor Honda : (Studi Kasus pada CV. Apollo Motor Pematang Siantar) - Kristina Mesya Yulianti Siburian; Edison Sagala (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of After Sales Service and Personal Selling on Purchasing Decisions for Honda Motorcycles at CV. Apollo Motor Pematang Siantar. This study uses a quantitative method with a sample size of 120 respondents through a purposive sampling technique. Data collection was carried out using a questionnaire with an ordinal scale and analyzed statistically through hypothesis testing using path analysis on SPSS 26 software. The results of the study indicate: (1) After sales service results in an increase in purchasing decisions for purchasing Honda motorcycles at CV. Apollo Motor Pematang Siantar; (2) Personal selling results in an increase in purchasing decisions for purchasing Honda motorcycles at CV. Apollo Motor Pematang Siantar; and (3) that After sales service and Personal selling result in an increase in purchasing decisions for purchasing Honda motorcycles at CV. Apollo Motor Pematang Siantar.